2015
DOI: 10.1007/s11947-015-1609-6
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds and Enzymatic Activity of Red Vegetable Smoothies During Storage

Abstract: Changes in the polyphenoloxidase (PPO), peroxidase (POD), pectinmethylesterase (PME) and phenylalanine ammonia-lyase (PAL) activities, total phenolics content (TPC) and total antioxidant capacity (TAC) on two red fresh vegetable smoothies (R1 and R2) based on tomato, red pepper, broccoli and carrot stored at 5 and 20°C were monitored. A conventional thermal treatment of 3 min at 80°C was applied to extend shelf life. The initial PPO, POD, and PME activities of R1/R2 smoothies (58/83, 0.023/0.020, and 1.50/0.38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 49 publications
(45 reference statements)
6
41
1
4
Order By: Relevance
“…At 45 days of storage, the sample had a reduction in the polyphenol content from 14 to 28% for samples stored at 10 and 25 °C. Rodríguez-Verástegui et al (2016) studied the change in polyphenol content of two vegetable smoothies composed of tomato, red pepper, broccoli and carrot when stored at 5 and 20 °C. The initial polyphenol content was from 40.4 to 46.2 mgEAG/100 g and, after 40 days of storage, the polyphenol content had a reduction from 13-18% at 5 and 20 °C, respectively.…”
Section: Anthocyanin and Polyphenol Contentsmentioning
confidence: 99%
See 1 more Smart Citation
“…At 45 days of storage, the sample had a reduction in the polyphenol content from 14 to 28% for samples stored at 10 and 25 °C. Rodríguez-Verástegui et al (2016) studied the change in polyphenol content of two vegetable smoothies composed of tomato, red pepper, broccoli and carrot when stored at 5 and 20 °C. The initial polyphenol content was from 40.4 to 46.2 mgEAG/100 g and, after 40 days of storage, the polyphenol content had a reduction from 13-18% at 5 and 20 °C, respectively.…”
Section: Anthocyanin and Polyphenol Contentsmentioning
confidence: 99%
“…Anthocyanin degradation was 56% soon in the first 45 days the samples were exposed to non-refrigerated storage conditions. Rodríguez-Verástegui et al (2016) have reported a reduction of 56% in antioxidant activity of vegetable smoothies composed of tomato, red pepper, broccoli and carrot when stored at 20 °C after 40 days.…”
Section: Anthocyanin and Polyphenol Contentsmentioning
confidence: 99%
“…TAC extraction and analysis were conducted using the same instruments and methodology described by Rodrı´guez-Vera´stegui et al (2015) using three different methods: free radical scavenging capacity with 2,2-diphenyl-1-picrylhydrazil (DPPH) (Brand-Williams et al, 1995), ferric reducing antioxidant power (FRAP) (Benzie and Strain, 1999) and 2,2 0 -azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) (Cano et al, 1998). All TAC data were expressed as mg of Trolox equivalents kg À1 fw.…”
Section: Chlorophylls Contentmentioning
confidence: 99%
“…Often, some smoothies may include other components like yogurt, milk, ice cream, lemonade or tea. They have a milk shake-like consistency that is thicker than slush drinks (Rodrı´guez-Vera´stegui et al, 2015). Recent research has shown that daily consumption of green smoothies may enhance health quality of consumers (Maeda, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our data on days 28 and 35, Keenan et al (2010) reported TAC (by FRAP) decreases of 19 % in heat-treated (70°C for 10 min) fruit smoothies after 30 days at 4°C. The TAC of treated samples progressively decreased during storage at 5 and 20°C, resulting in TAC levels that were 19-23 and 8-11 % lower after 58 and 40 days, respectively (Rodríguez-Verásteguil et al 2015). High power/short time MWP treatments resulted in the lowest TAC reduction at the end of the storage period (21 %), while the combination of low power/long time MWP and CP treatments registered the highest TAC reduction, around 27 and 28 % respectively, compared to their initial values.…”
Section: Total Antioxidant Capacitymentioning
confidence: 99%